Relative humidity measured at the Argentinean–German Geodetic Observatory (AGGO), 2018-2021 - Antico, Pablo Luis; Vera, José; Pasquaré, Alfredo; Galván, Romina; Häfner, Michael; Gende, Mauricio; Brunini, Claudio; Güntner, Andreas; Schröder, Stephan (PANGAEA, 2023)
Relative humidity measurements obtained from different sensors are used to construct a unique time series with one minute time-interval. Apart from differences in design and environmental exposition, periods of missing data also exist in the data series of each sensor. A primary data set was selected in terms of quality and temporal extension. A combination of two different techniques is applied to complete this data set: one is based on the autocorrelation of the series and the other on measurements taken from other sensors. The resulting values constitute a complete series of relative humidity at AGGO.
Keywords: meteorological data; relative humidity; South America